2021
DOI: 10.21037/atm-20-4576
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis as a risk factor for chronic obstructive pulmonary disease: a systematic review and meta-analysis

Abstract: Background: Prior pulmonary tuberculosis (TB) can cause permanent changes in lung anatomy and is associated with lung function loss. However, it remains unclear whether pulmonary function impairment owing to TB is associated with airflow obstruction, the hallmark of chronic obstructive pulmonary disease (COPD). The aim of this systematic review and meta-analysis was to assess the association and quantify the magnitudes of association between pulmonary TB and COPD, and to evaluate the prevalence of COPD in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 48 publications
(28 reference statements)
7
20
2
1
Order By: Relevance
“…In the present study with a rigorous sampling design and strictly quality control, we found a nearly 1.31 time increase in risk of airflow obstruction in post-TB subjects after adjusting for confounders, and a stronger association in never smokers (OR: 1.37; 95% CI 1.04 to 1.78). Besides, airflow obstruction was present in 21.3% of post-TB cases, which are consistent with a recent meta-analysis reporting a pooled prevalence of COPD in patients with post pulmonary TB of 21% (95% CI: 16% to 25%)5 and another study from low- income and middle- income countries reporting COPD was more common (25.7%) among those with previous tuberculosis than those without a history of tuberculosis 6. Therefore, for vast majority of patients after TB, the development of adjuvant interventions to prevent or to suspend further deterioration of lung function in individuals with post-TB could be an essential tool.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study with a rigorous sampling design and strictly quality control, we found a nearly 1.31 time increase in risk of airflow obstruction in post-TB subjects after adjusting for confounders, and a stronger association in never smokers (OR: 1.37; 95% CI 1.04 to 1.78). Besides, airflow obstruction was present in 21.3% of post-TB cases, which are consistent with a recent meta-analysis reporting a pooled prevalence of COPD in patients with post pulmonary TB of 21% (95% CI: 16% to 25%)5 and another study from low- income and middle- income countries reporting COPD was more common (25.7%) among those with previous tuberculosis than those without a history of tuberculosis 6. Therefore, for vast majority of patients after TB, the development of adjuvant interventions to prevent or to suspend further deterioration of lung function in individuals with post-TB could be an essential tool.…”
Section: Discussionsupporting
confidence: 90%
“…While smoking remains the key risk factor for chronic obstructive pulmonary disease (COPD), a considerable burden of the disease in low-income and middle-income countries cannot be explained by smoking alone. TB and other non-smoking risk factors of COPD such as domestic pollution are of increasing importance 3–6. An association between past TB and airflow obstruction, characteristic of COPD, has been reported in large population-based epidemiological studies 7–10.…”
Section: Introductionmentioning
confidence: 99%
“… 9 In a meta-analysis, the pooled prevalence of COPD in individuals with previous pulmonary tuberculosis was 21%. 37 In the China Pulmonary Health (CPH) Study, the overall prevalence of tuberculosis history in COPD individuals was less than 5.0%, 3 which was much lower than the prevalence in our study. However, a pooled analysis of individual data from the PREPOCOL-PLATINO-BOLD-EPI-SCAN studies showed that the prevalence of previous tuberculosis in individuals living at altitude >1500 m above sea level was significantly lower than those living at altitude <1500 m. 38 Three studies included in this pooled analysis were from Latin American regions and this result was inconsistent with our study.…”
Section: Discussioncontrasting
confidence: 72%
“…Many infectious respiratory pathogens are known to result in chronic respiratory disorders including chronic obstructive respiratory disease (COPD; a potential late consequence of tuberculosis, histoplasmosis, etc.) and asthma (which can manifest after childhood Respiratory Syncytial Virus infection) ( 12 , 13 ). Though less well-known, parasitic infections—from protozoa like Trypanosoma cruzi (an infection that manifests as Chagas disease, leading to the development of cardiomyopathy or GI disease in 30% of infected individuals) and Trypanosoma brucei (an infection that causes sleeping sickness, leading to chronic neurologic disease in Sub-Saharan Africa) to helminths—can also increase one’s risk for NCDs ( 14 ).…”
Section: The Global Impact Of Non-communicable Diseasesmentioning
confidence: 99%